2021
DOI: 10.1007/s10571-020-01032-9
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Expression of Rabies Virus Glycoprotein in the Rat Hippocampus Strengthens Synaptic Plasticity

Abstract: Rabies virus (RABV) is a neurotropic virus exclusively infecting neurons in the central nervous system. RABV encodes five proteins. Among them, the viral glycoprotein (RVG) plays a key role in viral entry into neurons and rabies pathogenesis. It was shown that the nature of the C-terminus of the RABV G protein, which possesses a PDZ binding motif (PBM) modulates the virulence of the RABV strain. The neuronal protein partners recruited by this PBM may alter host cell function. This study was conducted to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…In agreement with this proposal, a recent study showed that a peptide derived from RVG, which contains a snake toxin-like sequence, changes synaptic transmissions and motor behavior through blocking acetylcholine receptors (Hueffer et al, 2017). In addition, we recently showed that RVG strengthens both short-and longterm synaptic plasticity in the hippocampal dentate gyrus suggesting that it may alter synaptic function through both pre-and postsynaptic mechanisms (Ghassemi et al, 2021). In line with theses evidences, we found in the present study that RVG expression in the dorsal hippocampus facilitates spatial learning and memory.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In agreement with this proposal, a recent study showed that a peptide derived from RVG, which contains a snake toxin-like sequence, changes synaptic transmissions and motor behavior through blocking acetylcholine receptors (Hueffer et al, 2017). In addition, we recently showed that RVG strengthens both short-and longterm synaptic plasticity in the hippocampal dentate gyrus suggesting that it may alter synaptic function through both pre-and postsynaptic mechanisms (Ghassemi et al, 2021). In line with theses evidences, we found in the present study that RVG expression in the dorsal hippocampus facilitates spatial learning and memory.…”
Section: Discussionsupporting
confidence: 77%
“…This suggestion is supported by numerous reports indicating modulation of synaptic transmission by RABV including ion channel dysfunction (Iwata et al, 1999), aberrant neurotransmission (Ceccaldi et al, 1993;Dumrongphol et al, 1996;Ladogana et al, 1994), and changes in the electroencephalography of rabies patients (Gourmelon et al, 1991). Furthermore, in the previous study we showed that lentiviral expression of the rabies glycoprotein enhances synaptic transmission in the hippocampal dentate gyrus region (Ghassemi et al, 2021). Another clue that strengthens changes in synaptic function by RABV is that RABV increases release of neurotransmitters including serotonin and catecholamines in the hippocampus of the infected mice for a period of 1 week after infection with a peak on the day 3 (Fu and Jackson, 2005).…”
Section: Introductionsupporting
confidence: 83%
“…The neural protein partners recruited by PBM may change the function of host cells. Ghassemi et al [65] believed that the expression of RABV G promoted both short-and long-term synaptic plasticity in the hippocampal dentate gyrus (DG), suggesting that it may involve presynaptic and postsynaptic mechanisms to alter synaptic function.…”
Section: The Pathogeni Mechanisms Of Rabv G Proteinmentioning
confidence: 99%
“…In vivo field potentials were recorded according the previously established method 30 . In order to record from DG, a bipolar stimulating electrode (A-M Systems, USA) was implanted at the perforant path (AP: 8.1 from bregma, ML: 4.3 from bregma, DV: 3.3 from dura), and a monopolar electrode was fixed at DG stratum granulosum (AP: 3.8 from bregma, ML: 2.4 from bregma, DV: 3–3.5 from dura) as recording electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The optimum stimulus was applied every 5 min for 30 min to record baseline synaptic activity. For inducing long term potentiation (LTP), a HFS, consisting of 10 trains of 20 pulses at 400 Hz for DG 30 , 31 and at 200 Hz for CA1 32 , with 80% of maximum intensity was delivered every 10 s, (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%